Lipoprotein-associated phospholipase A₂ mass level is increased in elderly subjects with type 2 diabetes mellitus - Fortunato, Joao; Bláha, Vladimír; Bis, Josef; Šťásek, Josef; Andrýs, Ctirad; Vojáček, J; Jurašková, Božena; Sobotka, Luboš; Polanský, Pavel; Brtko, Miroslav (Journal of diabetes research, 2014)
OBJECTIVE. Lipoprotein-associated phospholipase A₂ (Lp-PLA₂) is extensively expressed by advanced atherosclerotic lesions and may play a role in plaque instability. We selected a group of elderly subjects that underwent transcatheter aortic valve implantation (TAVI) or balloon angioplasty (BA) and separated them into two groups, diabetic and nondiabetic, to compare the level of Lp-PLA₂ mass between them. METHODS. 44 patients aged 79.6 ± 5.6 years with symptomatic severe aortic valve stenosis underwent TAVI (n = 35) or BA (n = 9). 21 subjects had confirmed type 2 diabetes mellitus. Lp-PLA₂ mass was measured using an enzyme-linked immunosorbent assay kit (USCN Life Science, China) before and 3 days after the procedure. RESULTS. Lp-PLA₂ mass was significantly elevated in this population (1296 ± 358 ng/mL before TAVI; 1413 ± 268 ng/mL before BA) and further increased after TAVI (1604 ± 437 ng/mL, P < 0.01) or BA (1808 ± 303 ng/mL, P < 0.01). Lp-PLA₂ mass was significantly increased on the diabetic group before these interventions. CONCLUSION. Lp-PLA₂ may be a novel biomarker for the presence of rupture-prone atherosclerotic lesions in elderly patients. Levels of Lp-PLA₂ in diabetic patients may accompany the higher amount of small dense LDL particles seen in these subjects.
Keywords: Aortic Valve Stenosis; Female; biologické markery; Heart Valve Prosthesis Implantation; aortální chlopeň; Biomarkers; Diabetic Angiopathies; aortální stenóza; ženské pohlaví; Up-Regulation; průřezové studie; Aging; chirurgická náhrada chlopně; Diabetes Mellitus, Type 2; lidé; balónková angioplastika; upregulace; aterosklerotický plát; diabetes mellitus 2. typu; Aged, 80 and over; následné studie; 1-Alkyl-2-acetylglycerophosphocholine Esterase; stupeň závažnosti nemoci; Atherosclerosis; Cross-Sectional Studies; Follow-Up Studies; Male; Aged; stárnutí; diabetické angiopatie; ateroskleróza; Aortic Valve; senioři nad 80 let; senioři; mužské pohlaví; Severity of Illness Index; Plaque, Atherosclerotic; Angioplasty, Balloon; 1-alkyl-2-acetylglycerofosfocholinesterasa; Humans